Optimized mechanised rice harvesting in Southeast Asia - CGIAR Research Program on Rice (2019)
The innovation has been applied in alignment with the dissemination activities of IRRI-led projects helped to foster the combine harvester adoption in the countries. Rice harvesting is now almost fully mechanised in Vietnam and Cambodia. It is also progressing fast in the Philippines, Myanmar, and Laos.